IMAGES OF THE “RUSSIAN WINTER” AND “WINTER MOSCOW” IN THE REVELATION OF THE IMAGINATIVE SERIES OF “RUSSIA” IN “MOSCOW DIARY” BY WALTER BENJAMIN - Zhanna, Bril; Tatyana, Bodrova; Ekaterina, Nazartseva (Revista Inclusiones, 2020)
The article discusses the features of the embodiment in “Moscow Diary” Walter Benjamin figurative series of Russia. The article attempts to substantiate the author's position of Walter Benjamin in the perception and image of Russia. The conceptual content of the imaginative series of Russia and the specifics of its creation in the pages of its “Moscow texts” (diary, essay, review and essay) are analyzed with reference to the latest scientific data.